PERAN PUSTAKAWAN DALAM MENINGKATKAN MINAT KUNJUNG SISWA KE PERPUSTAKAAN PADA SMAN 2 PAMEKASAN - Admaja, Dyah Ayu Puspita Dita (MPI STAI Sangatta Kutai Timur, 2024)
The library is a place that contains all types and various fields of knowledge so that it is used as a learning resource. The aim of writing this article is to provide information to readers regarding the role of llibrarians in increasing students' interest in visiting the library at SMAN 2 Pamekasan. In writing this article, the author used descriptive qualitative research methods. Qualitative descriptive is the process of describing the results of a problem that occurs around you. The data collection techniques used by the author are observation,interviews, and literature study. Meanwhile, in data analysis, the author uses data reduction, data presentation, and conclusion. Theresults of this article are (1) Librarians provide services in the form of reference services, circulation services, provision of reading materials, arrangement of shelves, maintenance of facilities, and provision of internet access. (2) Efforts to increase interest in visiting include providing new and varied reading materials, providing services, and providing facilities and promotions. (3) Librarians must be able to establish good relationships with the school community to increase interest in visiting. (4) Factors that can influence visitor interest are health, fitness, interest, environment, facilities, motivation, and technology. (5) The challenges faced by librarians in visiting interests are competition between technologies, poor perception, lack of promotion, minimal collection of reading materials, lack of an OPACsystem, and lack of audio-visual media.